Catheter-directed thrombolysis in management of postpartum lower limb deep venous thrombosis – A case series - B.C. Srinivas (Indian Heart Journal, 2015)
Deep vein thrombosis (DVT) is a major health problem in pregnancy and postpartum period. Catheter-directed thrombolysis (CDT) is safe and effective in the management of symptomatic DVT. Value of CDT in postpartum DVT is not fully evaluated. We describe five patients presenting with acute iliofemoral DVT in their early postpartum period who were treated with mechanical thromboaspiration and CDT. The CDT was done using streptokinase infusion and unfractionated heparin. Percutaneous angioplasty was done in patients with symptomatic residual lesion following thrombolysis. Patients were discharged with oral anticoagulant and compression stockings. This approach was successful in all five cases. Percutaneous endovascular therapy using CDT, mechanical thromboaspiration, and balloon angioplasty is safe and effective in iliofemoral DVT in postpartum period.